The economic burden of overweight and obesity in Brazil: perspectives for the Brazilian Unified Health System. (June 2022) - Ferrari, G.; Giannichi, B.; Resende, B.; Paiva, L.; Rocha, R.; Falbel, F.; Rache, B.; Adami, F.; Rezende, L.F.M.
Abstract: Objectives: Parallel to rising obesity prevalence in Brazil, there is expected to be increased direct health care costs related to non-communicable diseases (NCDs). In this study, we estimated the economic burden of NCDs attributable to overweight and obesity in the Brazilian Unified Health System (SUS). Methods: We used self-reported body mass index of 85, 715 adults from the 2019 Brazilian National Health Survey. Annual costs (1 US = 2.281 Reais) with inpatient and outpatient procedures were obtained from the Hospital and Ambulatory Information Systems of the Brazilian SUS. Relative risks for cardiovascular disease, chronic respiratory disease, neoplasm, digestive disease, musculoskeletal disorders, diabetes and kidney diseases, sense organ diseases, and neurological disorders were retrieved from the Global Burden of Disease study. Results: Annually, US 654 million (95% uncertainty interval: US 418.4 to US 893.2) direct health care costs related to NCDs were attributable to overweight and obesity. Attributable costs were higher in women than men. Cardiovascular diseases had the highest attributable costs (US 289 million), followed by chronic respiratory diseases (US 110 million), neoplasms (US 96 million), digestive diseases (US 60 million), musculoskeletal disorders (US 44 million), diabetes and kidney disease (US 31 million), sense organ diseases (US 22 million) and neurological disorders (US 11 million). Conclusions: Overweight and obesity account for US 654 million direct costs of NCDs annually. Effective policies to promote healthy body weight may have economic benefits.